2015
DOI: 10.1016/j.cub.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

A Convergent and Essential Interneuron Pathway for Mauthner-Cell-Mediated Escapes

Abstract: The Mauthner cell (M-cell) is a command-like neuron in teleost fish whose firing in response to aversive stimuli is correlated with short-latency escapes [1-3]. M-cells have been proposed as evolutionary ancestors of startle response neurons of the mammalian reticular formation [4], and studies of this circuit have uncovered important principles in neurobiology that generalize to more complex vertebrate models [3]. The main excitatory input was thought to originate from multisensory afferents synapsing directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(135 citation statements)
references
References 45 publications
6
129
0
Order By: Relevance
“…To do this, we generated zebrafish larvae expressing YFP-tagged ChR2 (Lacoste et al, 2015) specifically in the DRN neurons. In tg(tph2:Gal4ff; 14xUAS-E1b:hChR2(H134R)-EYFP) larvae, ChR2 expression was restricted to the DRN and did not include other serotonergic populations (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…To do this, we generated zebrafish larvae expressing YFP-tagged ChR2 (Lacoste et al, 2015) specifically in the DRN neurons. In tg(tph2:Gal4ff; 14xUAS-E1b:hChR2(H134R)-EYFP) larvae, ChR2 expression was restricted to the DRN and did not include other serotonergic populations (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…To test the sufficiency of th2+ neurons for the initiation of swimming, we expressed Channelrhodopsin-2 (ChR2) in these cells by crossing Tg(UAS:ChR2-YFP) a144 [21] and Tg(th2:Gal-VP16) zd202 fish (Figure S1E) Expression of the ChR2-YFP fusion protein specifically in posterior recess neurons allowed us to examine their axon trajectory and targets using whole-brain confocal imaging (Figure 3J; Movie S3). We found that a majority of axons appear to terminate a short distance from the posterior recess, likely in the posterior tuberculum.…”
Section: Resultsmentioning
confidence: 99%
“…However, they also report observations indicating that SFNs may synapse with other cells and that their role in the circuit could be more complex. LaCoste et al, (2015) also examined the spiral fiber neurons and their role in the startle circuit. In this study, neurogenetic activation and ablation techniques were used to test hypotheses of SFN function.…”
Section: Spiral Fiber Neurons and Dissecting The Roles Of Hindbrain Cmentioning
confidence: 99%
“…One possible explanation is that SFNs synapse with cells other than the M-cell and loss of those connections is also associated with the aberrant bending. Although no additional connections of the SFN axons were observed by LaCoste et al, (2015), assessing the full complement of processes and connections is challenging.…”
Section: Spiral Fiber Neurons and Dissecting The Roles Of Hindbrain Cmentioning
confidence: 99%